Effectiveness of Sociodrama Intervention on Specific Phobic Fear and Involuntary Reactions in Children with a Secure Psychological Safe Haven - Marzban, Mahsa; Anasseri, Mehryar (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to determine the effectiveness of sociodrama intervention on specific phobic fear and involuntary reactions in children with a secure psychological safe haven. This study employed a quasi-experimental method with a two-group pretest–posttest design. The statistical population consisted of all children with a secure psychological safe haven in Tehran who had referred to the Andisheh Kian Talent Identification Institute in 2025. In the present study, 24 children with a secure psychological safe haven were selected using a purposive non-random sampling method and were then randomly assigned into an experimental group (n = 12) and a control group (n = 12). The experimental group participated in ten 120-minute sociodrama intervention sessions, and ultimately, after attrition, 11 participants successfully completed the treatment process. In contrast, the control group received no intervention. It should be noted that, in order to maintain equivalence between the experimental and control groups, a number of participants equal to the attrition rate in the experimental group were randomly removed from the control group as well. In this study, the revised version of the Screen for Child Anxiety Related Emotional Disorders (SCARED) and the Children’s Anxiety Scale were used. The collected data were analyzed using multivariate analysis of covariance (MANCOVA) and univariate analysis of covariance (ANCOVA). The findings indicated that there was a significant difference between the posttest mean scores of the experimental and control groups, and that the sociodrama intervention significantly improved specific phobic fear and involuntary reactions. Therefore, sociodrama intervention was effective in improving specific phobic fear and involuntary reactions in children with a secure psychological safe haven.